(untitled) (Web of Technology: Multidimensional Research Journal, 2026)
The following article analyzes methods for determining fuel consumption under various operating conditions of motor graders and examines how diesel fuel consumption during the operation of motor graders in mountainous areas depends on several factors. The main advantage of the regressive (determination and forecasting) model and the process of simultaneously assessing the influence of several factors on fuel consumption are also shown.